Pengaruh Kredit terhadap Pendapatan pada KPN Dharma Wiguna Pemerintah Kota Denpasar - Cok Istri Ratna Sari Dewi; Luh Putu Lusi Setyandarini Surya; I Gusti Ayu Ratih Permata Dewi; Putu Yudha Asteria Putri (Jurnal Riset Akuntansi, 2019)
One of the business product lines of cooperative is credit. Credit is one of the sources of income for cooperative. This study aims to find the the source of cooperative income and the effect of credit on income in the Civil Servant Cooperative (KPN) of Denpasar City Government. This study used a quantitative causal research design. The data collection technique used the documentation method while the data analysis technique used is simple regression analysis. The results showed that the source of income of the cooperative came from two types of businesses, Unit Simpan Pinjam and Unit Waserda, credit has a positive and significant effect on KPN’s income of Denpasar City Government.